Early Intervention of Kindergarten Children at Risk for Developmental Disabilities: A Greek Paradigm - Tzouriadou, Maria; Vouyoukas, Constantinos; Anagnostopoulou, Eleni; Michalopoulou, Lito E. (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Internationally most of the children at risk for developmental disabilities (intellectual disabilities, learning disabilities and language impairments) are detected within preschool settings. In Greece there are no early intervention services mandated nationwide. In practice, not detailed guidance and support is given to preschool teachers regarding the assessment and intervention of children at risk. This study provides research evidence from the implementation of an early intervention program in inclusive kindergartens, which is part of the practical training of students from the Faculty of Preschool Education Sciences, Department of Psychology and Special Education, Aristotle University of Thessaloniki, Greece. Response to intervention, as applied to kindergartens, was used to detect children not responding to core kindergarten curriculum. An inclusive early intervention educational program was implemented based on children’s profiles of strengths and weaknesses. At risk children participated in large group classroom activities with all children. For these children a specialized inclusive program with emphasis on school readiness was implemented. For children with developmental disabilities, an intensive individualized program was implemented, which put emphasis on the improvement of their cognitive abilities and socialization.